[PP.27.09] ROLE OF AMBULATORY BLOOD PRESSURE MONITORING IN SCREENING FOR SECONDARY HYPERTENSION. (September 2017) - Stojanovic, M.; Nisic, T.; Ciric, J.; Stojkovic, M.; Savic, S.; Beleslin, B.; Parapid, B.; Stojanov, V.; Zarkovic, M.
Abstract : Objective: Since the development of ambulatory blood pressure monitoring (ABPM), various studies have shown to be a very useful method in cardiovascular risk assessment and remains the only method of diagnosing a non- dipping blood pressure profile. It has been suggested that all forms of secondary hypertension, including renal/renovascular, glucocorticoid and mineralocorticoid excess, phaeochromocytoma and toxaemia in pregnancy are associated with blunted, eliminated or reversed nocturnal blood pressure fall. Design and method: We analysed 1621 patients referred to the Clinic of Endocrinology to be examined for secondary etiology of hypertension. ABPM revealed 268 subjects with white coat hypertension (WCH) so we didn't screened them for secondary hypertension. Meditech ABPM 05 device was used with appropriate cuff. We did all necessary analysis and tests in 1353 patients to see the aetiology of hypertension. The mean age was 42.6+/−10.8 years. There were 820 women and 533 men. Mean body mass index was 27 +/−8 kg/m 2 . Results: Screening for secondary hypertension revealed 68 patients with renovascular disease, 25 patients with all forms of hyperaldosteronism, 18 patients with pheochromocytoma including multiple endocrine neoplasia, 22 patients with glucocorticoid excess, 92 patients with obstructive sleep apnea. ABPM showed blunted or eliminated circadian blood pressure rhythm in 60 patients with renovascular disease or renal artery stenosis, 22 patients with all forms of hyperaldosteronism, 9 patients with pheochromocytoma including multiple endocrine neoplasia, 18 patients with glucocorticoid excess, every one of 92 patients with obstructive sleep apnea had blunted, eliminated or reversed nocturnal blood pressure fall. Conclusions: Results of our study indicate that nocturnal BP decrease was blunted or absent in a majority of patients with adrenal cause of hypertension. Nocturnal BP fall measured by ABPM may be very sensitive predictor of cardiovascular outcome and good method for screening for secondary hypertension.